An Ergonomic Desk and Chair Prototype to Improve Seating Position on Senior High School Students at Kabupaten Gresik - Neffrety Nilamsari; Soebijanto Soebijanto; Lientje S.M.; Setokoesoemo B.R. (Jurnal Ners, 2015)
Introduction: The need of desks and chairs at school which appropriate with student’s anthropometry are very important. Desks and chairs which not suit with student’s anthropometry will lead to fatigue. At Kabupaten Gresik, the provision of desks and chairs which suit with student’s anthropometry still less in number. This study was aimed to provide recomendation for an ergonomic desk and chair prototype to improve seating position on senior high school students at Kabupaten Gresik.Methods: This was preexperiment research with one group pre post test design. Research subjects were students at SMAN 1 Menganti and SMAN 1 Cerme, Kabupaten Gresik, 139 students were involved.Results: The recomendation of ergonomic desks and chairs specifi cation according to student’s anthropometry were: 1) Prototypechair N, length = 48 cm, wide = 43 cm, cushion base’s height from floor surfaces = 47 cm, bag keeper’s height from floor surfaces =3cm, bag keeper’s wide= 43 cm, bag keeper’s length = 47 cm, cushion’s wide = 41 cm, cushion’s length = 46cm, handrest’s height = 22 cm, handrest’s length = 30 cm, backrest’s height = 38 cm, backrest’s wide = 43 cm, cushion’s foam thickness = 4 cm, backrest’s foam thickness = 4 cm; 2) Prototype desk N, length = 50 cm, wide = 66 cm, back section’s height = 85 cm, front section’s height = 75 cm, footrest from fl oor surfaces = 10 cm, drawer’s height = 10cm, front bamper’s height = 40 cm, and table’s angle = 10o.Conclusion: An ergonomic desks and chairs are very important for students at school, it will help teaching learning process run well and comfortable. The measurement of desk and chair must be reviewed after fi ve years, because of student’s anthropometric development. So then students will feel no fatigue.